Effectiveness of using mixed ligand complexes of Zinc, Manganese and Cobalt in feeding dry stable cows - Kropyvka, Yurij; Bomko, Vitalii; Tytariova, Olena; Smetanina, Olena (Acta Scientiarum. Animal Sciences, 2024)
The purpose of the investigation was to determine the optimal dose of mixed ligand complexes of zinc, manganese, and cobalt in the ration of dry stable cows in the first and second dry periods. To cover the deficiency of Zinc, Manganese and Cobalt, different levels of mixed ligand complexes of Zinc, Manganese and Cobalt were introduced into the premix. During the dry period, the feeding of cows undergoes changes. During the early dry stable period in cows, feed mixtures with the lowest content of biologically active substances should be used for their feeding, namely, in 1 kg of DM, mg: Zinc and Manganese - 31.5; Cobalt - 0.41 due to mixed ligand complexes. Instead, during the late dry period, they need a higher concentration of these trace elements due to mixed ligand complexes in dry matter: Zinc and Manganese - 35 mg; Cobalt - 0.49 mg. A mandatory condition is to ensure the indicated level of trace elements due to their mixed-ligand complexes. With such feeding, a decrease in the need for labor assistance, the length of the service period and the number of inseminations per successful fertilization, an increase in the productivity.